Evaluation of flavor properties in rice bran by solid-state fermentation with yeast - Yuehui Wang; Huixin Liang; Zhongyuan Hu; Lei Chen; Lijie Zhu; Kun Zhuang; Wenping Ding; Qian Shen (Food Chemistry: X)
Rice bran (RB) as an available agricultural by-product is currently underutilized due to its susceptibility to oxidation and rancidity. This study investigated the evaluation of flavor properties in RB by solid-state fermentation with yeast (Saccharomyces cerevisiae). The volatile compounds (VOCs) in fermented RB were detected by chromatography-ion mobility spectrometry (GC-IMS), and headspace solid-phase microextraction gas chromatography–mass spectrometry (HS-SPME-GC–MS). A total of 76 volatile compounds (VOCs) including 10 aldehydes, 6 ketones, 9 alcohols, 20 esters, 10 hydrocarbons, 10 acids, and 11 compounds from other classes were identified. The odor intensity of RB fermentation by yeast was enhanced, especially for sulfides, hydrocarbons, and aromatic compounds. The fermented rice bran (FRB) exhibited a more diverse aroma profile, characterized by wine-like, fruity, and sweet odors, which significantly improved the overall sensory qualities of RB. This study provided the fermentation method for rice processing to promote the deep processing of by-products for more food resources.